Utilizing Liner Artificial Intelligence Image Recognition for identifying Skin Disorders in Skin of Color - Ryan Scheinkman; Alexia Vignau; Ricardo Cooke; Daniel Green; Philippe Jean-Pierre; Keyvan Nouri (International Journal of Medical Students)
BACKGROUND: Advances in artificial intelligence (AI) with machine learning have allowed for the use of this technology to identify the contents of images and answer questions about the contents of the images. Technologies, such as artificial intelligence, offer a potential avenue to improve medical care to marginalized communities. In this study we attempted to see how well the Liner AI model was able to detect ten dermatological diseases from Skin of Color images of the diseases.